Reputation lasts longer than life: How can central banks quantify their reputational risk? - Pradip Kumar Kafle (Journal of Central Banking Theory and Practice, 2023)
It takes multiple decades of commitment and credibilityto create repute but only a few seconds to tarnish it, as the instancesof misinformation, disinformation and malinformation galore. Inlight of this, Central banks, as delicate and sensitive public institu-tions, are significantly vulnerable to such reputation risk due to theirmandate for policy decisions and implementation. Thus, this studyaims to formulate a barometer that quantifies the reputation score ofcentral banks. The Central Bank Reputation (CBR) score is derivedbased on the respondents' responses to a questionnaire that includestwelve attributes and twenty-eight indicators, which is administeredamong the eight set of audiences. The reputation score ranges from-100 to +100, that indicates the reputation of the Central Bank at apoint of time. The deviation in reputation score between two pointsof time thus measures the reputational risk. However, the study sug-gests applying other qualitative analysis tools in complement withthis quantitative barometer, to come up with the robust assessment.
Keywords: E5; E52; E58; 330; Credibility; Risk Management; Reputational Risk; Reputational Barometer